Molecular survey of Cytauxzoon spp. and Hepatozoon spp. in felids using a novel real-time PCR approach - Grillini, Marika; Beraldo, Paola; Frangipane di Regalbono, Antonio; Dotto, Giorgia; Tessarin, Cinzia; Franzo, Giovanni; Marchiori, Erica; Modrý, David; Simonato, Giulia (Frontiers in Veterinary Science, 2023)
Tick-transmitted apicomplexans of genera Cytauxzoon and Hepatozoon affect a wide range of felids worldwide but knowledge of them is still scant. Recently, several studies addressed the species circulating in Europe, distribution and hosts. Molecular assays are the methods of choice for their detection. Unfortunately, conventional PCRs already described are time and cost-consuming and specific either for Hepatozoon or Cytauxzoon detection. This survey was developed in order to evaluate i)the occurrence of Cytauxzoon and Hepatozoon in felids using a fast and cost-saving real-timePCR able to detect simultaneously both protozoa, ii)the distribution of Cytauxzoon and Hepatozoon species in North-eastern Italy, and iii)the involvement of other susceptible felid hosts in the same area. A SYBR®Green based real-timePCR with primers targeting the 18S-rRNA was validated and applied to 237 felid samples, i.e. whole blood from 206 domestic cats and 12 captive exotic felids, and tissues from 19 wildcats. Positive results were achieved through the melting temperature curve analysis thank to the specific melting peak (i.e., 81°C Cytauxzoon spp.; 78-78.5°C Hepatozoon spp.). Positive samples were submitted to conventional PCR followed by sequencing for species’ identification. Phylogenetic analyses were performed to assess relatedness among European isolates. Data on domestic cats (age class, sex, provenance, management, lifestyle) were recorded and statistical analyses were performed to identify potential risk factors. Thirty-one/206 (15%) domestic cats were positive for Hepatozoon spp. (i.e., 12 H. felis, 19 H. silvestris) and 6/206 (2.9%) for C. europaeus. Hepatozoon felis prevalence was significantly (p < 0.05) higher in owned cats, while H. silvestris in stray cats and animals coming from Eastern region (i.e., Friuli Venezia Giulia). Cytauxzoon europaeus was detected in stray cats only from Friuli Venezia Giulia (Trieste province). Among captive felids, a tiger was infected by H. felis and another by H. silvestris; 8/19 (42%) wildcats were positive for Hepatozoon spp. (i.e., 6 H. felis, 2 H. silvestris) and 4/19 (21%) for Cytauxzoon europaeus. Outdoor lifestyle and provenance (i.e., Friuli Venezia Giulia region) were the most relevant risk factors for H. silvestris and C. europeus infection. Contrariwise, H. felis was most frequently isolated in owned cats suggesting different ways of transmissions.